Sistema basado en internet de las cosas para la gestión de los recursos de un aula de clases - Villafuerte Solórzano, Jonathan Stalin (2020)
IoT allows the interconnection of electrical and electronic devices to an Internet network, the same ones that communicate to provide a better lifestyle for those who use it, observing from a technical point of view, is a set of sensors that send signals to devices connected to fixed and wireless networks. The buildings are the ones that most attend this type of technologies, and thus make them innovative, for this reason, in actions to modernize the facilities of the State Technical University of Quevedo, a "Internet of Things Based System for the Management of The Resources of a Classroom Classes" was implemented. The objective is to intercommunicate the electronic and electrical devices of a given space, giving full control of the on and off of the artifacts to the authorized person who must perform authentication to access the course. Test-Driven Development Methodology for IoTS (TDDM4IoTS) was used to carry out this research, which enabled the development of the hardware-composite system, complemented by the IoT-based system composed of microcontrollers, single board computers, and power grid connection of the given space; and, the software that consists of a mobile application for the total control of these electrical and electronic devices. Adding digital academic features useful to the teacher such as registering their attendance and that of their students, gaining control of electrical and electronic devices, consulting assistance, requesting temporary permits to access a course, among others. For authentication, facial recognition was incorporated allowing the automatic opening of locks, as long as the teacher has assigned schedule and subjects to the classroom that he wants to access; and thus, decreased the waiting time on the part of the teacher for a third person to help him with this activity. Keywords: Internet of Things, authentication, facial recognition, domotic.